Simulation of a Psychological Decision Process in Personnel Selection - Smith, Robert D.; Greenlaw, Paul S. (Management Science, 1967)
Considerable attention in recent years has been given to the computer simulation of human thought processes in problem solving. This paper describes the computer simulation of the decision processes of a psychologist dealing with the ill-structured problem of analyzing psychological test scores and other data concerning individuals being considered for various types of clerical and clerical-administrative positions. The computer model was designed to output, as did the psychologist in his decision making, both: (1) numerous interpretive comments about each applicant, and (2) a specific recommendation as to whether the individual should be employed. The methodology and results of this research are described, and the possibility of utilizing computerized models of this type as an aid in personnel selection is suggested.